The effects of peeling and cooking on the mineral content and antioxidant properties in carrots enriched with potassium iodate and/or selenite (SeIV) and selenite (SeVI). (16th November 2016) - Bieżanowska-Kopeć, Renata; Pysz, Mirosław; Kapusta-Duch, Joanna; Kopeć, Aneta; Smoleń, Sylwester; Koronowicz, Aneta; Piątkowska, Ewa; Rakoczy, Roksana; Skoczylas, Łukasz; Leszczyńska, Teresa
Abstract: Research covered six variants: control, unfertilized carrots and carrots fertilized with: KIO3, Na2 SeO4, Na2 SeO3, KIO3 and simultaneously with Na2 SeO4, and fertilized with KIO3 and simultaneously Na2 SeO3 . Carrots enriched with iodate or selenite, or both iodate and selenite, were characterized by higher amount of these minerals. Changes to the content of micro- and macroelements, during the cooking time of the carrots, both in peeled and unpeeled carrots, did not head in the same direction (increase, decrease and no change). However, cooking an unpeeled carrot generally resulted in the increased content of polyphenol and carotenoids. On the other hand, cooking peeled carrots led to a decrease in the content of polyphenol and a general lack of change in carotenoid content in relation to the unpeeled cooked carrot. During cooking, the antioxidant activity of the carrot being assessed changed together with the direction of changes in polyphenol content but not in line with the direction of changes in carotenoids.